Study on surface roughness and geometrical tolerances of Inconel 718 superalloy polished by magnetic abrasive finishing process. (January 2023) - Khoshanjam, Ali; Azizi, Abdolhamid; Bahrami, Pooya; Khoshanjam, Keyvan
Magnetic Abrasive Finishing (MAF) is an advanced finishing process that has the prominent characteristics such as the ability to machine complex surfaces with complex geometry. Geometric tolerances are among the important parameters in the qualitative evaluation of machining parts. Due to the large number of abrasive edges participating in the finishing process, it is very difficult to achieve accurate geometric tolerances in the MAF process. This problem is especially considerable in workpieces with low machinability such as nickel based superalloys. In this study, the effect of process input parameters such as feed rate, rotational speed, and working gap on surface roughness and geometric parameters such as circularity and cylindricity of the external surfaces of an Inconel 718 shaft was investigated. The results indicate that surface quality and geometric tolerances improve with increasing rotational speed. However, the increase of rotational speed by a certain amount leads to turbulence in the movement of abrasive particles and no significant changes are seen. As well as, by increasing feed rate, surface roughness and geometric tolerance increase. Furthermore, with the working gap increasing due to the reduction of magnetic abrasive brush width, circularity, and cylindricity tolerances increase, but smoother surface roughness is achieved.